UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA PADA PELAJARAN AKIDAH AKHLAK MATERI AKHLAK TERPUJI DENGAN METODE SOSIODRAMA DI MI DARUL IMAN MUARALEMBU KELAS V - Dedi Erwan (Universitas Riau, 2023)
The purpose of this class action research is to improve student learning outcomes by using the Sociodrama method for grade V students of Madrasah Ibtidaiyah Darul Iman Muaralembu in the subject of Akidah Akhlak praiseworthy morals. The subjects of this study were grade V students of MI Darul Iman Muaralembu, totaling 21 students in the 2021/2022 school year. The data collection techniques in this study were tests, interviews, observations, field notes and documentation. The results showed an increase in students' learning achievement, namely in cycle I of 67.4%, in cycle II it increased to 81.2%. This means that there was an increase of 26.4%. thus the use of the Sociodrama method in Akidah Akhlak subjects can improve student learning achievement.